Curved carbon plates inside running shoes modified foot and shank angular velocity improving mechanical efficiency at the ankle joint - Miyazaki, T.; Aimi, T.; Yamada, Y.; Nakamura, Y. (Journal of Biomechanics, 2024)
Recent technologically advanced running shoes have been designed with higher stack height and curved carbon plate-reinforced toe springs to enhance running performance. The purpose of this study was to examine how curved carbon-plate reinforcement modulated mechanical efficiency at the ankle joint during the running stance phase. We prepared two footwear conditions: Non and Carbon, both had a 3D-printed midsole (40-mm heel thickness). A full-length curved carbon plate was inserted along the toe spring in Carbon. The participants included 14 non-rearfoot long-distance athletes. They were required to run at a speed of 12 km/h on a 20-m runway with both shoes. Mechanical-energy expenditure (MEE, indicating mechanical work) and compensation (MEC, indicating mechanical efficiency) were calculated in the following mechanical-energy transfer phases: concentric, eccentric, and no-transfer. Running with Carbon exhibited improved MEC and reduced MEE at the ankle joint during the concentric transfer phase than with Non. The improvement in the concentric MEC at the ankle joint indicates that a larger amount of mechanical energy is transferred from the shank into the foot segment that compensates for the force exerted by the plantar flexor muscles, which implies more mechanically efficient plantarflexion movement. As the ankle joint is the largest energetic contributor in the running stance phase, greater MEC and lower MEE and torque at the ankle joint could improve running performance. Hence, the curved carbon plate may be a key feature of advanced footwear technology.